Pregnancy Success Rates by Different Assisted Reproductive Techniques in Tubal, Ovarian, and Sperm Disorders - Zeinab Hajaliakbari Hafezabad; Milad Ahmadi Gohari; Faezeh Kashi (Iran University of Medical Sciences, 2020)
Background: Assisted Reproductive Techniques (ART) have been used for addressing numerous causes of infertility. However, it remains unclear which kind of these methods are best for various infertility types. Accordingly, this study aimed at determining pregnancy success rates by different ART in tubal, ovarian, and sperm disorders. Methods: The present descriptive retrospective study used the records of individuals who had referred to the Infertility Center of Kerman University of Medical Sciences from March 2016 to December 2017. All subjects underwent Intracytoplasmic Sperm Injection (ICSI) and In Vitro Fertilization (IVF). The sperm parameters were assessed based on the criteria of the World Health Organization (WHO) for determining the causes of male infertility. The data were documented and compared with the criteria of the WHO. Then, they were analyzed by analysis of variance, Paired Samples t-test, Chi-squared, or Fisher's Exact tests using SPSS. Results: The overall Mean±SD fertility rate in IVF and ICSI was 4.28±2.87 and 3.62±2.54, respectively and the difference was not significant (t=1.02, P=0.319). There was a significant difference in the fertility rate due to tubal infertility (P=0.018) between ICSI and IVF; the fertility rate in the IVF method was significantly higher than that of the ICSI. The pregnancy rate in the freeze method was higher than those of the other methods (P<0.001). This discrepancy was also found in all causes of infertility. There was no significant difference in the disorders of sperm and the result of two methods (IVF/ICSI). Conclusion: The obtained results suggested that in the freeze method, the pregnancy rate was higher than other approaches; this discrepancy was found in all the causes of infertility. It is suggested that frozen-thawed embryo transfer be used in infertile individuals. This is because it increases the success rate of pregnancy and prevents complications due to the repeated use of infertility treatments and exorbitant treatment costs.